Cognitive Determinants Of Lexical Nucleology In A Comparative Perspective (Texas Journal of Philology, Culture and History, 2025)
This study offers a comparative examination of how lexical nuclei emerge and evolve through an interplay of cognitive schemas, morphological expansions, and sociohistorical factors in typologically distinct languages. Drawing on empirical data from English, Russian, Mandarin, and Spanish corpora, the analysis highlights universal cognitive constraints underlying core lexical clusters while revealing language-specific variations linked to morphological structure and usage frequency. Neurolinguistic evidence, such as ERP patterns, underscores how entrenched conceptual anchors shape semantic organization, providing a foundation for future interdisciplinary research that integrates computational models, psycholinguistic experimentation, and broader typological sampling